Academic institutional entrepreneurs in Germany: Navigating and shaping multi-level research commercialization governance - Liudvika Leisyte; Lisa Sigl (Triple Helix, 2018)
In this article, we aim to explore the agency of scientific entrepreneurs and research managers in shaping their Triple Helix contexts. Drawing on institutional documents and in-depth interviews with research managers and scientists in the German state of North Rhine-Westphalia, the study shows that trust in scientific entrepreneurs from research managers, their scientific standing and leadership, and type of academic entrepreneurship are central in shaping the Triple Helix relationships. Research managers frame themselves as passive service-providers for scientists' commercialization activities while scientists see them as facilitating creative employment arrangements. Research managers perceive scientists as self-motivated highly creative risk-takers. The studied scientific entrepreneurs negotiate their institutional arrangements and find flexible solutions for the structural barriers within their research organisations. At the same time, they tend to avoid taking personal risks when it comes to contractual arrangements and their careers. The study identifies two types of agency exerted to shape the Triple Helix context-bricolage and institutional entrepreneurship. Bricolage activities and the trust of research managers in the leadership and autonomy of scientific entrepreneurs prepare the basis for institutional change. This can be the ground for institutional entrepreneurship to take place and reshape the Triple Helix relationships in the particular context.
Keywords: 330; Academic entrepreneurship; Institutional entrepreneurship; Individual agency; Research commercialization governance